Asy-Syaikh Ahmad Fauzan wa Hamasatuhu al-Jihadiyyah fi Ad-Difai 'An Jumhuriyyati Indonesia al-Muwahiddah. - Zubaidi Masyhud (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2017)
Abstract:This study aims to explore the role of women in strengthening the foundations of the Islamic family in the context of Indonesia. It examines the responsibilities and contributions of women in maintaining the harmony and stability of the family institution based on the teachings of Islam. The research employs a qualitative approach, utilizing interviews, observations, and analysis of relevant literature. The findings highlight the significant role of women in nurturing the values of faith, morality, and compassion within the family. Furthermore, their contributions in raising children with strong Islamic values and promoting a supportive and loving environment are crucial in building a strong Islamic family. The study concludes by emphasizing the importance of empowering women and recognizing their contributions in order to strengthen the foundations of the Islamic family in Indonesian society. Keywords: Women, Islamic family, roles, contributions, Indonesia